Identifikasi Kebutuhan Penggunaan Teknologi Artificial Intelligence (AI) dalam Mendukung Pembelajaran Matematika yang Adaptif - Tyaningsih, Ratna Yulis; Gilang Primajati; Eka Kurniawan (FKIP Universitas Mataram, 2024)
This study aims to identify the need for the use of Artificial Intelligence (AI) technology in supporting adaptive mathematics learning. The subjects of this research are students of the Faculty of Teacher Training and Education, University of Mataram, who are enrolled in mathematics courses. This is a descriptive study with a qualitative approach. The data collection instruments used are observation and questionnaires. The results of this study indicate that: (1) 96% of students are accustomed to using Artificial Intelligence (AI) technology for learning, with 31% reporting usage